Implementation of Pancasila Student Profiles in Islamic Religious Education (PAI) Learning - Kirana Silkia Maulida; Badrus Zaman; Rojif Mualim (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2023)
This study aims to explain how the Pancasila Student Profile is implemented in the Islamic Religious Education (PAI) curriculum at Salatiga State Vocational School and the methods used to strengthen character according to the Pancasila Student Profile. This research uses a type of qualitative research with a descriptive approach. The methods used are observation, documentation, and interviews to collect data. Before data analysis, the steps followed were data reduction, data presentation, drawing conclusions, and verification. The study results show that: (1) The Pancasila Student Profile is applied in PAI learning by applying habits according to the indicators of the Pancasila Student Profile. (2) The methods used to strengthen the character according to the Pancasila Student Profile in PAI learning include incorporating the Pancasila Student Profile into the subject matter, fostering student discipline, giving good advice and examples from the teacher, explaining ethics to students, emphasizing the meaning of Islam and its application in everyday life. as well as encouraging activities such as congregational prayers, Duha prayers, and reading the Koran. Pancasila Student Profile, if applied in accordance with the indicators set, students will have a character that is in line with the noble values of Pancasila.